Using Image Processing of A Fabry -Perot Interferometer to Determine the Defects of Leneses by Using He-Ne Laser - Habaua, S.A. H (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A design of a Fabry -Perot  interferometer system was constructedto determine the precise value of the wavelength which is required in spectml studies depending on varying medium pressure where the refractive  index  was a  function  of  pressure  at  a  constant  distance between  the  two  mirrors by  using a Hc-Ne  laser (632.8)  tun as  a coherent source .The (fmee) (t) and the coefficient of finesses (F) and the visbilityof the fringes (V) has been calculated  . Image processing \\â€¢as used and   its  result   can   be   relied   on   verifying   the  defects   of   the manuli1ctured lenses used in the optical instruments.